188 A Case of Hairy Cell Leukemia Uncharacteristically Presents With Absolute Monocytosis as a Manifestation of a Concurrent Myelodysplastic/Myeloproliferative Neoplasm. (11th January 2018) - Williams, Todd; Taute, Lindsay; Dunlap, Jennifer; Fan, Guang
Abstract: A 77-year-old man with no disclosed hematologic abnormalities presents with splenomegaly, lymphadenopathy, and weight loss. CBC reveals absolute monocytosis, mild normocytic anemia, and thrombocytopenia, and is otherwise normal. A peripheral blood smear shows a marked abundance of monocytes, immature monocytes, dysplastic neutrophils, dysplastic erythrocytes, and a population of lymphocytes with morphologic features consistent with hairy cell lymphocytes. Flow cytometry on the peripheral blood reveals two distinct cell populations within the monocyte gate. One population shows a characteristic monocytic immunophenotype, and the other population expresses immunophenotypic markers consistent with hairy cell lymphocytes. A bone marrow biopsy reveals diffuse infiltration and replacement by hairy cell leukemia and minimal fibrosis. The overriding presence of hairy cell leukemia obscures the ability to evaluate for myelodysplastic/myeloproliferative histologic alterations. Genetic studies performed on the peripheral blood reveal BRAF V600E and KRAS p.G12D mutations. Hairy cell leukemia characteristically presents with monocytopenia. The unusual presence of monocytosis, the myelodysplastic findings in the peripheral blood, and KRAS mutations raise suspicion for a concurrent myelodysplastic/myeloproliferative neoplasm, likely chronic myelomonocytic leukemia or atypical chronic myelogenous leukemia. It is not unusual for a concurrent malignancy to coexist with hairy cell leukemia as multiple sources have shown that the rate of additional malignancy in hairy cell leukemia is significantly increased compared to the general population. The diagnosis of a concurrent myelodysplastic/myeloproliferative neoplasm could not be definitively made because the prevailing presence of hairy cell leukemia obscures any myeloid abnormalities that may be present in the bone marrow histology.